Transaksi Kredit dalam Perspektif Hukum Islam: Menelusuri Batas Halal-Haram antara Riba, Bunga Bank, dan Praktik Syariah - Abu Alim (JSE: Jurnal Sharia Economica, 2025)
This study discusses credit transactions from an Islamic legal perspective with a focus on the halal and haram boundaries between usury, bank interest, and sharia credit practices. The background is the increasing use of credit systems in modern society which are often colored by interest practices, causing polemics among scholars regarding their legal status. This study uses a qualitative-descriptive approach with a literature study from the perspectives of classical and contemporary scholars, MUI fatwas, and the practices of financial institutions. The results show that conventional credit transactions have the potential to contain usury if there are unauthorized additions, while sharia-based credit systems, such as murabahah and ijarah, are considered halal as long as they meet the principles of justice, transparency, and are free from exploitation. The implications of this study direct Muslims to understand contracts correctly, distinguish between interest and profit margins, and choose sharia-compliant financial institutions as a solution to economic needs without violating religious provisions.